The validity of the Decree of Members of the Regional House of Representatives (DPRD) as a Credit Guarantee for the Bank Jatim - Ita Primaria Lestari; Moh Saleh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Loans are one of the main functions of banks in their operations by asking for the surrender of collateral, problems arise if the decree of appointment of DPRD cannot be qualified as a collateral object. Then the bank must base Article 1b and 1c of the Decree of the Board of Directors of Bank Indonesia N 23/69 / KEP / DIR on February 28, 1991, concerning Credit Provision Guarantees stated that the bank's trust in the debtor's ability to repay the loan in accordance with what was promised. Article 3 The decree stipulates that guarantees can be in the form of goods, projects or claim rights financed with credit, and other items, securities or risk guarantees added as additional collateral. 2) Legal Position of Appointment of DPRD Member Decree Credit agreement at Bank Jatim is a binding guarantee (only as an authentic document that must be fulfilled), which arises because of the underlying agreement.